Spatial variation of life-history traits in Bulinus truncatus, the intermediate host of schistosomes, in the context of field application of niclosamide in Côte d’Ivoire - Cyrille K. Konan; Yves-Nathan T. Tian-Bi; Nana R. Diakité; Mamadou Ouattara; Jean T. Coulibaly; Diabaté Salia; Amani Koné; Adolphe K. Kakou; Rufin K. Assaré; Mocket A. Ehouman; Sonya C. Glitho; Eliézer K. N’Goran (BMC Zoology, 2022)
Abstract Background Control of intermediate host snails using molluscicides for the control and/or elimination of schistosomiasis is a strategy in line with WHO recommendations. Niclosamide is the main chemical molluscicide recommended by WHO. However, except the immediate killing of the snail, the extent of the impact of the molluscicide application on the evolution of snail life-history traits, in relation to recolonization of treated sites is not well known. This study aimed to characterize the spatial variation of life-history traits of populations of the freshwater snail Bulinus truncatus, in relation to niclosamide spraying in the field. From 2016 to 2018, we conducted a trial, using niclosamide to control the intermediate host snails for interrupting the seasonal transmission of urinary schistosomiasis in northern and central Côte d’Ivoire. Five villages (sites) were considered, including three test and two control villages. In the test villages, the molluscicide was sprayed in habitats harboring B. truncatus snails three times a year (November, February–March and June). We sampled six B. truncatus populations: two populations from the control villages without any treatment; one collected before treatment and three sampled 2–3 months after treatment of the site with niclosamide. The snail populations were monitored for several life-history traits, including survival, growth, fecundity and hatchability, under laboratory conditions, over one generation (G1). We tested the population, region (North/Centre) and treatment status (treated/untreated) effects on the variation of the measured life-history traits and correlations between pairs of traits were estimated. Results On the whole, the traits varied among populations. The risk of death was lower in northern populations compared to central ones. The age at first reproduction was reached earlier with a smaller size of snails in northern populations. Values of first reproduction features (size and fecundity) were lower in treated snail populations. The overall growth of untreated populations was higher than that of treated ones. The late fecundity and egg hatching were higher in northern than in central snails. At first reproduction, age was negatively correlated with some fecundity parameters. However, growth was positively associated with fecundity. Conclusions Our study showed a spatial variation of life-history traits in B. truncatus snails. The mollusciciding seems to have led to the depression of some life-history traits in the snail populations. However, investigations should be carried out over several generations of snails to better clarify the impact of niclosamide on the evolution of the life-history traits.